Analysis of Factors Associated with the Incidence of Unmet Need in Women of Reproductive Age - Yulizawati, Yulizawati; Fitria, Henni; Oktova, Rafika; Mardhiah, Radhiyatan; Silmi, Harridhil (Universitas Andalas, 2024)
Background: Rapid population growth is a pressing concern with widespread implications, including potential food and energy crises. To address this issue, the Indonesian government has implemented Family Planning (FP) programs. However, the total fertility rate (TFR) continues to rise. A high unmet need for family planning is a significant contributing factor. Unmet need for family planning is defined as the percentage of women of reproductive age, whether married or in a union, who have an unmet need for family planning. Purpose: The aim of this study was to determine the factors associated with the incidence of unmet need among women of reproductive age at the Padang City Community Health Center. Method: A cross-sectional methodology and analytical observational study design were used. The study included 95 non-pregnant women of reproductive age in Padang City. The sample size was determined using a quota sampling approach. Data were analyzed using the Chi-Square test with a 95% Confidence Interval (CI). Results: The results indicated that the p-value was 0.000, which is ≤ 0.05, indicating a significant correlation between knowledge, attitude, and the incidence of unmet need. Conclusion: These findings suggest that addressing these factors could be an effective strategy for decreasing the incidence of unmet need among women of reproductive age. Health providers need to raise awareness about family planning and enhance women's understanding of the importance of utilizing family planning services